Increased prevalence of abnormal vertebral patterning in fetuses and neonates with trisomy 21. (18th July 2019) - Schut, Pauline C.; Ten Broek, Clara M. A.; Cohen-Overbeek, Titia E.; Bugiani, Marianna; Steegers, Eric A. P.; Eggink, Alex J.; Galis, Frietson
Abstract: Purpose: To assess the prevalence of an abnormal number of ribs in a cohort of fetuses and neonates with trisomy 21 and compare this with a subgroup of fetuses without anomalies. Materials and methods: Radiographs of 67 deceased fetuses, neonates, and infants that were diagnosed with trisomy 21 were reviewed. Terminations of pregnancy were included. The control group was composed of 107 deceased fetuses, neonates, and infants without known chromosomal abnormalities, structural malformations, infections or placental pathology. Cases in which the number of thoracic ribs or presence of cervical ribs could not be reliably assessed were excluded. The literature concerning vertebral patterning in trisomy 21 cases and healthy subjects was reviewed. Results: Absent or rudimentary 12th thoracic ribs were found in 26/54 (48.1%) cases with trisomy 21 and cervical ribs were present in 27/47 (57.4%) cases. This prevalence was significantly higher compared to controls (28/100, 28.0%, Χ 2 (1) = 6.252, p  = .012 and 28/97, 28.9%, Χ 2 (1) = 10.955, p  < .001, respectively). Conclusions: Rudimentary or absent 12th thoracic ribs and cervical ribs are significantly more prevalent in deceased fetuses and infants with trisomy 21.